(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: Industrialization of society and competitive lifestyle have made our daily life full of stress and people are searching for a convenient way to cope with this. Effect of lemongrass fragrance on brain functions can be analyzed through power spectral analysis of quantitative electroencephalogram (EEG). Objective: To assess the effects of lemongrass (Cymbopogon Citratus) essential oil aroma inhalation on EEG in healthy female adults in awake state by power spectral analysis. Methods: This self-controlled trial was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka from March 2022 to February 2023. Thirty healthy female volunteers from this campus participated in this study. Each subject had undergone three successive sessions of baseline, water and essential oil mist inhalation and EEG recording afterwards. Statistical test was done by Student’s paired ‘t’ test and Wilcoxon matched pair signed rank test by using SPSS v.25. Results: Mean ± SD of absolute power of alpha brain wave were significantly higher (p˂0.0001) after inhalation of essential oil mist compared to both baseline and water mist inhalation in all brain regions. The absolute power of beta wave after essential oil mist exposure was significantly higher compared to baseline and water mist exposure in frontal (p=0.0001; p=0.0005), parietal (p=0.0009; p=0.005) and occipital regions (p<0.001). No significant change after inhalation of water mist compared to baseline. Conclusion: Lemongrass essential oil inhalation is effective to induce conscious relaxation, calmness with increased attention and vigilance by increasing power of alpha and beta waves in healthy female adults. JAFMC Bangladesh, Vol 19, No 2 (December) 2023: 32-36